CHINA’S STRATEGY OF ENERGY SECURITY IN CENTRAL ASIA - Xing Li; Chenxin Wang (Сравнительная политика, 2015)
U.S.recently launched strategy of rebalancing to Asia worsens the atmosphere forChina’s energy security and increases the risks for energy transportation from Africa and theMiddle East. The diversification of energy sources is a reasonable strategic choice, so the importance of the Eurasian continent forChinaincreases. Central Asia does not play anymore a supporting role in the agenda ofChina’s energy security strategy. It is rather becoming a region of major strategic importance.